Philosophy of management and sustainability : rethinking business ethics and social responsibility in sustainable development - Rendtorff, Jacob Dahl (Bingley, U.K. : Emerald Publishing Limited, 2019)
Using an interdisciplinary focus, this book combines the research disciplines of philosophy, business management and sustainability to aid and advance both scholarly and practitioner understanding of sustainability management and the United Nations' Sustainable Development Goals (SDGs). As businesses and society continue to transition towards further sustainable development and corporate social responsibility, the key challenge faced is in rethinking the philosophy of management and business ethics to achieve this change in deep and lasting ways. Jacob Dahl Rendtorff explores the philosophical foundations of business ethics, economics and sustainability through four key themes: From CSR and business ethics to sustainable development goals (SDGs) Philosophy of management and ethical economy of sustainability Foundations of philosophy of management, ethics and sustainability Responsible management of sustainability. In reflecting on the works of philosophers and scholars such as Hannah Arendt, Paul Ricœur, Thomas Piketty and Peter Koslowski within the context of sustainability, globalization, anthropocene ethics and corporate social responsibility, the book presents a key understanding of the vital philosophical foundations for creating progressive business models in a more sustainable society.
Introduction -- I. From CSR and business ethics to sustainable development goals (SDGs) -- 1. Ethics and justice in the international world: the problem of globalization and the need for a cosmopolitan spirit -- 2. Sustainability and business ethics in a global society -- 3. Ethics of administration - towards sustainability and cosmopolitanism -- 4. Corporate social responsibility, sustainability, and stakeholder management -- 5. Business sustainability and the UN sustainable development goals (SDGs) -- II. Philosophy of management and ethical economy of sustainability -- 6. Philosophy of management and ethical interdependence in the Anthropocene age -- 7. Environmental catastrophe and challenges to ethical decision-making -- 8. From the financial crisis to a new economics of sustainability -- 9. Ethical economy and the environment -- 10. The concept of equality in ethics and political economy -- III. Foundations of philosophy of management, ethics and sustainability -- 11. The dark side of sustainability: evil in organizations and corporations -- 12. The ethics of integrity: a new foundation of sustainable wholeness -- 13. Recognition between cultures as the foundation of ethical and political sustainability -- 14. Philosophy of management in the hypermodern experience economy -- IV. Responsible management of sustainability -- 15. The principle of responsibility: rethinking CSR as SDG-management.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Business ethics; Sustainable development; Management -- Philosophy; Business & Economics -- Business Ethics; Business ethics & social responsibility